Co-opting and resisting market based instruments for private land conservation. (January 2018) - Cooke, Benjamin; Corbo-Perkins, Gabriella
Highlights: Landholders and ecologies can resist the market logic of underpinning MBIs for PLC. Many landholders wanted social interaction that the scheme did not facilitate. The market logic of tenders does not reflect the extent of landholder stewardship. The assumptions underlying payments for conservation must be thoroughly examined. Abstract: The increasing popularity of private land conservation (PLC) globally has quickly translated into an array of polices and programs aimed at achieving ecological benefits. The growth of PLC is entwined with the rise of neoliberal governance, with private land proving congruous with the promotion of market-based instruments (MBIs) and the reliance on private protected areas for conservation in lieu of government investment in public lands. Despite a growing literature on the implications of neoliberal environmental governance, there remains a need for specific insights into the way that individual landholders and ecologies can co-opt or resist the rationalities of MBIs in the practice of private land conservation. Through semi-structured interviews and property walks with 18 landholders, this research examines the implementation of a reverse-auction tender scheme called 'EcoTender' in Victoria, Australia. We uncovered four main tensions between the market logic of the program and conservation practice: 1) some landholders used the payment scheme to increase regulatory protections on their property through covenants/easements; 2) many landholders struggled to conceive of their stewardship practice as contractual labour; 3) landholders were producing novel ecosystems that challenged land management focused at the property parcel scale when EcoTender encouraged a return to historical benchmark ecologies, and; 4) many landholders wanted social collaboration when the program required competition for cost efficiency. Our insights show that PLC must create room for a diverse trajectory of conservation practice in dynamic socio-ecological contexts. This means careful reflection on the validity of assumptions underpinning MBIs, the trade-offs that come with applying market logic to conservation and the long-term implications of these instruments for policy and practice.